Identificação, expressão recombinante e caracterização de uma cisteíno peptidase de Diaphorina citri, inseto vetor da doença Huanglongbing - Ferrara, Taíse Fernanda da Silva (Universidade Federal de São Carlos, 2014)
Brazil is a major exporter of oranges in the world, with the state of São Paulo, the largest citrus producer in the country. In the last years plants of the genus citrus have been strongly affected by various diseases and among them, the disease Huanglongbing (HLB) have occupied prominent role and importance due to the devastating damage caused to citrus production worldwide. Caused by Candidatus Liberibacter spp., a bacterium that colonizes and blocks the conductive vessels of elaborated sap (phloem) and transmitted by the vector, hemiptera, the psyllid Diaphorina citri. In this context, it is necessary to search for strategies to control the disease in citrus orchards. In order to identify a cysteine peptidase D. citri, in this work, the identification, recombinant expression and characterization of a cysteine peptidase D. citri, the type (cathepsin B) called DiaciCATHB was performed. The identification of an ORF for cysteine peptidase was performed using the database of the transcriptome of D. citri. Recombinant expression was performed in Pichia pastoris yeast cells. For activation of the recombinant enzyme important factors were observed, acidic conditions and incubation in suitable temperature and time. Kinetic characterization of the enzyme was verified by hydrolysis of the synthetic substrate Z-Phe-Arg-MCA, resulting in a (km) of 15.7 mM. Inhibition of the enzymatic activity tests were conducted using the recombinant inhibitor of cysteine peptidases CaneCPI-4, resulting in the inhibition constant (Ki) of 0.05 nM. The analysis of gene expression DiaciCATHB demonstrated that gene expression occurs in all stages of insect development, there is however a significant difference in expression level. According to the developmental stages of the insect D. citri, the expression level gradually increases DiaciCATHB, being higher in nymph and adult stages. The present results do not prove that the location and function performed by the enzyme DiaciCATHB, but regardless, the cysteine peptidase in this study has the potential to become an important target for use in future studies on insect control.
Keywords: Enzimas; Cítricos; Cisteíno peptidase; Diaphorina citri; Catepsina B-like; Huanglongbing(HLB); CIENCIAS BIOLOGICAS::GENETICA